Sufism and Maqamat: The Transformation of the Soul in the Divine Dimension - Muh Idris (Sao Literasi Publisher, Yayasan Pendidikan Khaerul Munif, 2025)
This paper aims to deeply examine the concept of maqāmāt (spiritual stages) and various forms of Sufism such as ethical (akhlāqī), gnostic (‘irfānī), and philosophical (falsafī) Sufism within the Islamic tradition. Employing a qualitative-descriptive method based on library research, this study explores the historical roots, doctrinal development, and both internal and external factors that influenced the emergence of Sufism. Findings indicate that although there are influences from outside Islam, the essence of Sufism grows from core Islamic teachings—namely the Qur’an, Hadith, and the example of the Prophet Muhammad. The spiritual journey in Sufism is structured through maqāmāt such as repentance (tawbah), piety (wara’), asceticism (zuhd), patience (ṣabr), trust (tawakkul), acceptance (riḍā), love (maḥabbah), and divine knowledge (ma‘rifah). Moreover, the development of Sufism is influenced by the socio-political conditions of the Muslim community, such as responses to profane lifestyles, the rationalistic codification of Islamic law, and the quest for deeper spirituality. This study concludes that Sufism is not merely an individual mystical expression but also a social and spiritual response to the dynamics of the ummah. Sufism plays a significant role in shaping personal and communal piety through ethical and contemplative approaches.